A case of mucinous cystadenoma of appendix - C., Tharun Ganapathy; Chandrasekar, Shruthi; S., Jeyakumar (International Surgery Journal, 2017)
Mucocoele of the appendix is the term used to describe an appendix dilated with mucous collections due to benign or malignant causes. Primary tumors of the appendix are rare. Many a time, a mucocoele of the appendix is reported through histopathological study of the appendix removed in a scenario of acute appendicitis. 25% of the patients with mucocoele of appendix are asymptomatic, however patients may present with acute appendicitis or other obstructive symptoms. Here we report an unusual presentation of mucocoele of appendix who presented with chronic pain and mass in the right lower abdomen.